PERENDAMAN PLAT RESIN AKRILIK POLIMERISASI PANAS PADA EKSTRAK BUNGA ROSELLA (Hibiscus sabdariffa L.) TERHADAP PERUBAHAN WARNA - Wirayuni, Kadek Ayu (Interdental: Jurnal Kedokteran Gigi, 2019)
The color of acrylic resin plate is one of particular concern, because it's related with aesthetics of oral tissue. An acrylic resin can absorb colored fluids and cause a color change, which reduces the aesthetic value of the denture. This study aims to determine discoloration of acrylic resin plate heat cured after submersion of rosella flower extract. This study used 25 samples, divided into 5 samples for 20% rosella flower extract, 5 samples for 40% rosella flower extract, 5 samples for 60% rosella flower extract, 5 samples negative control (aquades) and 5 samples positive control (fifftydent). Soaking time is 10 minutes per day for a week. The type of research used was experimental pretest-posttest with control group design. Measurements using Adobe Photoshop and the CIELab color measurement system. Furthermore, statistically using the Shapiro wilk test, Leven's test, One Way Anova and Least Significant Diffence. The results of the study are shows the mean color change of CIELab (DE) in the five groups after treatment significantly different (p <0.05). Least Significant Difference - test (LSD) test shows the results of immersion test on extract 20% and 40% are not different from negative controls, extract 60% is different from negative controls, extract 60% is same like positive control. The conclusions in this study are concentration of immersion with rosella flower (Hibiscus sabdariffa L.) extract 20% and 40% can't change the color of the acrylic resin plate heat cured, however extract rosella flowers (Hibiscus sabdariffa L.) 60% can change the color of acrylic resin plate heat cured.